Optimalisasi Publikasi Ilmiah Bereputasi Internasional [Penyusunan Letter to Editor berbasis Artificial Intelegence]: [Drafting Letters to the Editor Using Artificial Intelligence] - HARINTO NUR SEHA; Noor, Ahmad Yani; Yulida, Rina; Nofitriyani, Nofitriyani; Wahyudi, Azis (Permata Indonesia, 2025)
The community service activity focused on increasing faculty publications through alternative channels such as Letters to the Editor in reputable journals, as a solution to the slow peer-review process for full articles. This activity was carried out through technical guidance that integrated the use of artificial intelligence technology, namely ChatGPT as a content writing tool, and Typeset.io as a reference search and formatting tool. The activity was held on Friday, July 25, 2025, in Room GW 6 of the Permata Indonesia Polytechnic, involving 19 lecturers from four study programs (Hospital Administration, Midwifery, Pharmacy, and Medical Records and Health Information). The evaluation method used a pre-test and post-test consisting of 10 questions to measure the increase in knowledge. The test results showed a significant increase in participants' knowledge after the technical training, as evidenced by an increase in the average score from 55 to 88,42. The discussion showed that the use of AI and digital tools can facilitate lecturers to contribute quickly to scientific discourse through LtE, while fulfilling their obligation to publish reputable works. This activity was concluded to have successfully improved lecturers' understanding and skills in publishing scientific ideas efficiently.